Pengaruh Penggunaan Flashcard Terhadap Penguasaan Mufrodat Bahasa Arab - Mutiara, Qholbi (Maliki Interdisciplinary Journal, 2024)
This article examines the influence of using flashcards as a learning media on mastery of Arabic mufrodat. The stigma that often arises about learning Arabic being difficult and boring requires teachers to evaluate the learning process. One alternative that is frequently used is the use of flashcards as a media that makes it easier for students to remember the vocabulary taught in learning Arabic mufrodat. This research was carried out using a qualitative approach. The data source used in this research is documents of student learning results before and after learning mufrodat using flashcards. The research results showed that there was a significant increase in students' mastery of mufrodat. Apart from that, students feel that learning mufrodat with flashcards is more fun and easier so that learning goals can be achieved.